(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
The earth’s surface temperature has increased by 1.5°C. One of the causes of rising global temperatures is greenhouse gases. Nationally, more emissions from the waste sector (54.4%) are produced by households than by industry. Medan City is the 4th largest city in Indonesia with a population density of 9,283 people per km2 and population density has a positive correlation with waste generation where waste generation is one of the sectors that sources GHG emissions. The purpose of this study is to analyze the influence of family economy (family income and expenses) on GHG emissions from the waste sector in households in Medan City The population consists of 523,097 households, with a sample of 270 houses. The seven selected sub-districts are Medan Deli, Medan Helvetia, Medan Marelan, Medan Denai, Medan Johor, Medan Amplas, and Medan Tembung. The inclusion criteria are households that do not have a business or agricultural/livestock activities. The sampling method was incidental sampling. The smallest total family income in Medan City is Rp 1,000,000 and the highest is Rp 25,000,000. The smallest total family expenditure is IDR 1,000,000 and the highest is IDR 15,000,000. There is an effect of income on GHG emissions from the waste sector in households in Medan City (Sig.2 tailed < 0.05). The strength of the relationship between emissions and GHG emissions in the waste sector is weak with a non-directional relationship. Likewise, the effect of income on GHG emissions from the waste sector in households in Medan City.